Pathways of Resurgence: Considering L’nuwey Tplutaqan (Mi’kmaw law) in Mi’kma’ki - McMillan, L. Jane (2022)
This is the 9th event of the Comparative Law Series The Mi’kmaw Nation is no stranger to Canadian injustice. Donald Marshall, a Mi’kmaq man from Nova Scotia, was wrongly convicted of murder in 1971. He served 11 years of a life sentence. In 1989, a Royal Commission into his prosecution made 82 recommendations to fix the problem of racial discrimination in the justice system through changes in the administration of justice, and policing, and in developing Mi’kmaq justice services. Twenty-five years later, a thorough review found a very disappointing record of implementation of the recommendations, particularly those dealing with the development of Mi’kmaq led justice services, and to ongoing experiences of systemic discrimination an overrepresentation in the criminal justice system. Mi’kmaw communities continue to call for a reinvigoration of their traditional legal principles and practices as the best ways to address the problems of systemic discrimination and racism, to decolonize the Canadian justice system, and to legitimize self-determining Indigenous legal institutions. Merely Indigenizing the Canadian justice system is an inadequate alternative: same paint, new brush. Instead, Mi’kmaw peoples are reclaiming and restoring L’nuwey Tplutaqan. In this presentation, Dr. L. Jane McMillan discusses the pathways of resurgence of Mi’kmaw legal principles and processes in Mi’kma’ki. UVic Graduate Student Law & Society Research Group Faculty Unreviewed